2020
DOI: 10.3390/condmat5020024
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Correlation of THz Pulses from the Electron Storage Ring BESSY II

Abstract: Coherent synchrotron radiation from an electron storage ring is observed in the THz spectral range when the bunch length is shortened down to the sub-mm-range. With increasing stored current, the bunch becomes longitudinally unstable and modulates the THz emission in the time domain. These micro-instabilities are investigated at the electron storage ring BESSY II by means of cross-correlation of the THz fields from successive bunches. The investigations allow deriving the longitudinal length scale of the micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Coherent synchrotron radiation from an electron storage ring is observed in the THz spectral range when the bunch length is shortened to the sub-mm-range. Schade and co-workers, in their contribution [32], showed that increasing the stored current in the ring causes the bunch to become longitudinally unstable and modulates the THz emission in the time domain. Their results set the limits for the possible time resolution of pump-probe experiments with coherent THz synchrotron radiation from a storage ring.…”
Section: Discussionmentioning
confidence: 99%
“…Coherent synchrotron radiation from an electron storage ring is observed in the THz spectral range when the bunch length is shortened to the sub-mm-range. Schade and co-workers, in their contribution [32], showed that increasing the stored current in the ring causes the bunch to become longitudinally unstable and modulates the THz emission in the time domain. Their results set the limits for the possible time resolution of pump-probe experiments with coherent THz synchrotron radiation from a storage ring.…”
Section: Discussionmentioning
confidence: 99%